2017
DOI: 10.1016/j.jadohealth.2016.10.428
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Antiretroviral Adherence Among Young Black Men Who Have Sex With Men

Abstract: HIV-positive young Black MSM (YBMSM) experience poor antiretroviral (ART) medication adherence relative to their white counterparts. However, few studies have longitudinally examined factors that may correlate with various classifications of ART adherence among this population, which was the primary aim of this study. Project nGage was a randomized controlled trial conducted across five Chicago clinics from 2012–2015. Survey and medical records data were collected at baseline, 3-, and 12-month periods to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…Young Latino MSM with HIV in our study reported that the use of alcohol and drugs influenced ART adherence interruptions, consistent with previous studies (Sauceda et al, 2018;Shubber et al, 2016;Voisin et al, 2017) and the individual-level factors proposed in the Social-Ecological Model (Bronfenbrenner, 1989). Our study adds a more in-depth understanding of the ways in which substance use disrupts adherence, namely through the after-effects of substance use (being intoxicated or high), through the intentional brief interruption or modification of ART pill-taking routine to accommodate substance-using event, and through prolonged interruptions of ART treatment during extended drug-using periods.…”
Section: Discussionsupporting
confidence: 91%
“…Young Latino MSM with HIV in our study reported that the use of alcohol and drugs influenced ART adherence interruptions, consistent with previous studies (Sauceda et al, 2018;Shubber et al, 2016;Voisin et al, 2017) and the individual-level factors proposed in the Social-Ecological Model (Bronfenbrenner, 1989). Our study adds a more in-depth understanding of the ways in which substance use disrupts adherence, namely through the after-effects of substance use (being intoxicated or high), through the intentional brief interruption or modification of ART pill-taking routine to accommodate substance-using event, and through prolonged interruptions of ART treatment during extended drug-using periods.…”
Section: Discussionsupporting
confidence: 91%
“…Use of marijuana is also significantly associated with providing partner names during PN interviews. Past studies point to marijuana’s mixed effects on HIV care engagement, with some correlating marijuana use with antiretroviral non-adherence, 27 and others finding no such relationship. 28 Yet marijuana use may improve partner information provision by reducing mental barriers caused by the stress and anxiety often associated with a new HIV diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified biological family, friends, and other natural mentors as important social connections and sources of support for YB-GBMSM (8, 9). At the dyadic level, social relationships have been successfully used to enhance medication adherence and retention in care among YB-GBMSM through identification of a support person within their existing networks (10, 11). Additionally, researchers have described unique endogenous social structures within YB-GBMSM communities such as the house/ball scene (in which groups called “houses” composed primarily of YB-GBMSM compete against one another in underground dance events known as “balls”) and surrogate “gay families” that provide important social resources for their members (12, 13).…”
Section: Introductionmentioning
confidence: 99%